Wastewater from the soft drinks industry as a source for bioethanol production - Isla, Miguel Angel (2013)
Wastewaters from the soft drinks industry were examined as media for producing bioethanol usingyeast-mediated fermentation. Fermentation assays were performed using cola-type, orange and lemon-lime soft drinks and the biomass, sugar and ethanol levels were monitored over time. The effect of the addition of yeast extract was evaluated; the results indicated that 15 g/L is a suitable value for successful fermentation. Depletion of the sugars contained in the soft drinks (10?12% w/v) was achieved in less than 12 h when the medium was inoculated with 2 g/L of Saccharomyces cerevisiae var. Windsor. Ethanol yields were close to the theoretical values. The performance of several kinetic models was evaluated,and their parameters were determined. A model including inhibition by ethanol enabled the best adjustment of the experimental results in all assayed media. Some soft drinks include sodium benzoate in their formulae, the effect of which on yeast metabolism is discussed.